Institutionality in Agroindustrial Chains.: Elements for The Design of Policies - Díaz Porras, Rafael (2018)
This article discusses the scope of agroindustry chains institutionality in the design of productive policies. In the first place, it is assumed the existence of a meso level in the productive chains, whose structure and scope have a specific impact on its competitive development and sustainability, which is determined by the nature ofthe organizations that lead the meso level and chain´s requirements. From both, the systemic competitiveness and global value chains perspectives, it is proposed that the meso level of the chains constitutes an instance that determines its productive policy making. The institutionality of the chains is linked to its productive structure, the production organizations, the nature of the product and the chain as a whole. Finally, with this framework, it is important to understand the challenges, contradictions and potential that face the institutionality of the chain to boost its competitiveness and sustainability.